2023
DOI: 10.1038/s41467-023-39346-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human TRPV4 in complex with GTPase RhoA

Abstract: Transient receptor potential (TRP) channel TRPV4 is a polymodal cellular sensor that responds to moderate heat, cell swelling, shear stress, and small-molecule ligands. It is involved in thermogenesis, regulation of vascular tone, bone homeostasis, renal and pulmonary functions. TRPV4 is implicated in neuromuscular and skeletal disorders, pulmonary edema, and cancers, and represents an important drug target. The cytoskeletal remodeling GTPase RhoA has been shown to suppress TRPV4 activity. Here, we present a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 71 publications
0
45
0
Order By: Relevance
“…Elucidation of the molecular pathways by which mutant TRPV4 channel activity alters NVEC tight junction integrity and barrier function will be an important focus for future work. We and others have shown that TRPV4 interacts with the small guanosine triphosphatase RhoA ( 14 , 16 , 17 ) and that motor neuron disease–causing mutations in TRPV4 disrupt this binding and the reciprocal inhibitory interactions between TRPV4 and RhoA ( 14 , 16 ) . Because RhoA activation can drive endothelial junctional complex disassembly by promoting actin cytoskeleton remodeling ( 51 , 52 ), these findings suggest a potential mechanism through which TRPV4 may regulate BSCB permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elucidation of the molecular pathways by which mutant TRPV4 channel activity alters NVEC tight junction integrity and barrier function will be an important focus for future work. We and others have shown that TRPV4 interacts with the small guanosine triphosphatase RhoA ( 14 , 16 , 17 ) and that motor neuron disease–causing mutations in TRPV4 disrupt this binding and the reciprocal inhibitory interactions between TRPV4 and RhoA ( 14 , 16 ) . Because RhoA activation can drive endothelial junctional complex disassembly by promoting actin cytoskeleton remodeling ( 51 , 52 ), these findings suggest a potential mechanism through which TRPV4 may regulate BSCB permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, each TRPV4 protomer comprises six transmembrane domains and intracellular N and C termini. Motor neuron disease–causing mutations occur primarily on the convex face of a prominent ankyrin repeat domain within the N terminus ( 5 , 14 – 17 ). In heterologous expression systems, mutant TRPV4 channels exhibit elevated channel activity ( 5 , 6 , 14 , 16 , 18 ), suggesting that TRPV4 antagonism may represent a therapeutic strategy for patients with TRPV4 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…b, examples of some types of cells that express TRPV4, along with their corresponding functions are depicted. PDB: 8T1B (3.0-Å resolution) [ 52 ]. Created with PyMOL and BioRender.com.…”
Section: General Properties Of Trpv4 Channelmentioning
confidence: 99%
“…Currently, we know that TRPV4 is assembled as a homotetramer [ 45 , 52 , 53 , 84 ]; although, it has been described that it can form heteromeric channels with the TRPP2 in an alternating 2:2 stoichiometry [ 39 ]; TRPC1 [ 85–88 ]; TRPC1 and TRPP2 [ 89 ], and most recently with TRPV3 [ 90 ].…”
Section: General Properties Of Trpv4 Channelmentioning
confidence: 99%
See 1 more Smart Citation